Effects of chronic home radon exposure on cognitive, behavioral, and mental health in developing children and adolescents - Taylor, Brittany K.; Pulliam, Haley; Smith, OgheneTejiri V.; Rice, Danielle L.; Johnson, Hallie J.; Coutant, Anna T.; Glesinger, Ryan; Wilson, Tony W. (Frontiers in Psychology, 2024)
It is well-established that chronic exposure to environmental toxins can have adverse effects on neuropsychological health, particularly in developing youths. However, home radon, a ubiquitous radiotoxin, has been seldom studied in this context. In the present study, we investigated the degree to which chronic everyday home radon exposure was associated with alterations in transdiagnostic mental health outcomes. A total of 59 children and adolescents ages 6-to 14-years-old (M=10.47 years, SD=2.58; 28 males) completed the study. Parents completed questionnaires detailing aspects of attention and executive function. We used a principal components analysis to derive three domains of neuropsychological functioning: 1) task-based executive function skills, 2) self-and emotionregulation abilities, and 3) inhibitory control. Additionally, parents completed a home radon test kit and provided information on how long their child had lived in the tested home. We computed a radon exposure index per person based on the duration of time that the child had lived in the home and their measured home radon concentration. Youths were divided into terciles based on their radon exposure index score. Using a MANCOVA design, we determined whether there were differences in neuropsychological domain scores across the three groups, controlling for age, sex, and socioeconomic status. There was a significant multivariate effect of radon group on neuropsychological dysfunction (λ=.77, F=2.32, p=.038, ηp 2 =.12). Examination of univariate effects revealed specific increases in self-and emotion-regulation dysfunction among the youths with the greatest degree of chronic home radon exposure (F=7.21, p=.002, ηp 2 =.21). There were no significant differences by group in the other tested domains. The data suggest potential specificity in the neurotoxic effects of everyday home radon exposure in developing youths, with significant aberrations in self-and emotion-regulation faculties. These findings support the need for better public awareness and public health policy surrounding home radon safety and mitigation strategies.